2000
DOI: 10.1002/1097-4695(20000915)44:4<414::aid-neu4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in neuron numbers in the hippocampal formation of a food-hoarding bird: The black-capped chickadee

Abstract: The volume of the hippocampal formation (HF) in black-capped chickadees (Poecile atricapillus) varies across the seasons, in parallel with the seasonal cycle in food hoarding. In this study, we estimate cell density and total cell number in the HF across seasons in both juveniles and adults. We find that the seasonal variation in volume is due to an increase in the number of small and large cells (principally neurons) in the fall. Adults also have lower neuron densities than juveniles. Both juveniles and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 63 publications
5
65
2
Order By: Relevance
“…This seemed to complement the results of Barnea and Nottebohm (1994). Smulders et al (2000), however, concluded that this change in volume was related to an increase in the total number of neurons in the hippocampus. Barnea and Nottebohm did not find seasonal changes in total neuron number, only in the number of new neurons.…”
Section: Experience Seasonality and Neurogenesis In Birdssupporting
confidence: 61%
See 2 more Smart Citations
“…This seemed to complement the results of Barnea and Nottebohm (1994). Smulders et al (2000), however, concluded that this change in volume was related to an increase in the total number of neurons in the hippocampus. Barnea and Nottebohm did not find seasonal changes in total neuron number, only in the number of new neurons.…”
Section: Experience Seasonality and Neurogenesis In Birdssupporting
confidence: 61%
“…Lavenex et al (2000a,b) found no seasonal variations in hippocampal volume, total neuron number, or cell proliferation rates in the adult scatter-hoarding eastern gray squirrel (Sciurus carolinensis), an interesting contrast with the results from birds (Smulders et al 1995(Smulders et al , 2000 in terms of seasonal changes in volume and neuron number. Barker et al (2005) compared the yellow pine chipmunk, both a lar-der-and scatter-hoarder, to the scatter-hoarding eastern gray squirrel during the fall when both species were actively collecting and storing food for winter.…”
Section: Role Of the Hippocampus In Mammalsmentioning
confidence: 96%
See 1 more Smart Citation
“…We do know that species-specific reactions to spatial experience (food storing or other spatial learning tasks) during development contribute to differences between some species of food-storing versus non-food-storing birds. In adults, food-storing experience alone does not appear to alter the volume of the Hp in some species (Cristol, 1996); although combined with other seasonal effects, it may increase Hp volume, cell number, or new cell recruitment in other species such as the black-capped chickadee (Barnea & Nottebohm, 1994;Smulders et al, 1995;Smulders, Shiflett, Sperling, & DeVoogd, 2000). Changes in Hp neuroanatomy across seasons that are correlated with seasonal demand for spatial memory appear to be triggered directly by changes in photoperiod in some mammals (Prendergast, Nelson, & Zucker, 2002).…”
mentioning
confidence: 99%
“…As mentioned previously, some songbirds store food reserves during the autumn and winter. In one such species, the black-capped chickadee, mitotic neurons migrate into the adult hippocampus (Barnea and Nottebohm 1996), thereby increasing hippocampal volume via changes in neuron number (Smulders et al 1995(Smulders et al , 2000; but see Hoshooley and Sherry 2004). Importantly, peaks in hippocampal recruitment occur in good temporal agreement with increases in foodstoring and retrieval.…”
Section: Estrogens and Adult Neurogenesismentioning
confidence: 99%